Rubidium marking reveals different patterns of movement in four ground beetle species (Col., Carabidae) between adjacent alfalfa and maize. (17th November 2015) - Madeira, Filipe; Pons, Xavier
Abstract: In the north‐east Iberian Peninsula, in summer, arable crop landscapes are characterized by a mosaic of alfalfa and maize. Although carabids are among the main predators in both crops, crop management can affect their movement. The main aim of the present study was to measure the movement of the four most abundant carabid species ( Calathus fuscipes, Poecilus cupreus, Bembidion lampros and Pseudoophonus rufipes ) between adjacent alfalfa and maize before and after alfalfa cutting, using rubidium as a marker. Movement of predators into the herbaceous margin between alfalfa and maize was also assessed. The four carabid species showed bidirectional movements between crops, although the pattern of movement differed between species and was affected by alfalfa cutting. After cutting, the movement of C. fuscipes, P. cupreus and P. rufipes from alfalfa towards maize was higher than in the opposite direction. Bembidion lampros showed a greater degree of movement towards alfalfa than in the opposite direction before cutting and only moved to the margin after cutting. Maize and herbaceous field margins can therefore act as both refuge and donor habitat for carabids, and can help to recolonize alfalfa after cuttings. Growing maize near alfalfa and providing an intercrop refuge habitat may conserve and enhance carabid populations.